PCR Based Detection of Cutaneous Leishmaniasis - Salman Hakim, Walayat Shah, Jamshed Khan, Jamshida Iqbal Khattak, Muhammad Idrees Khan, Muhammad Sohail, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The second most common illness after malaria that is transmitted by vectors and that may be lethal if untreated is leishmaniasis. Leishmaniasis is caused by parasites of the genus Leishmania, which are classified into two subgenera, Viannia and Leishmania. Methodology: A total of 100 sample collected from presumed clinically as CL patients by dermatologist, with 50 positive cases and 50 negative cases on Geimsa stain microscopy for Leishman Donovan (LD) bodies. After permission from Ethical board in Khyber medical university KPK and inform consent from patient or their guardian in case of children was taken. The lesion and its surroundings were cleaned with 70% ethanol, and the fluid oozing out of the first prick was obtained and disperse over a glass slide, left to dry and fixed with methanol, and stained with Giemsa stain. Two pricks were administered with a sterile BD syringe at the active margin of the lesion. The second prick's fluid was collected and kept in an EDTA tube for PCR usage at -20°C at the IBMS laboratory of KMU in Peshawar. Results: Out of 100 CL patients, 53 were female and 47 were male. The patients age was ranged from two year to 89 year. PCR was positive in 64 cases and negative in 36 cases out 100 for CL. Out of 50 positive microscopic cases 37cases were positive on PCR. Out of 50 microscopic negative cases 27 (54%) were positive by PCR. A statistically significant difference was found between PCR and microscopic method in the detection of CL. Conclusion: The finding in our study specifies that PCR base analysis is superior to microscopy for diagnosis of CL. Therefore, we recommend use of PCR for the detection of CL along with Giemsa staining in order to improve the quality and sensitivity of routine diagnosis of the disease. Keywords: Polymerase Chain Reaction, Giemsa staining, Cutaneous leishmaniasis